Pesticide Safety Miniposter: Pesticide Emergencies - Rebecca W. Baldwin; Stephanie K. Hill; Philip Koehler; W. Walker; J. C. Medley (EDIS)
This poster introduces new pest control technicians to the general actions to be taken in the event of pesticide exposure. Technicians learn to recognize symptoms of exposure as they watch videos linked to the quick response (QR) codes on the poster. The videos detail general first aid steps to undertake until medical help arrives after a pesticide exposure. Designed by R.W. Baldwin, S.K. Hill, Philip Koehler, W. Walker, and J.C. Medley, and published by the UF Department of Entomology and Nematology, August 2012.